The Explanation Related to the Relationship between Drug Abuse and Crime - gholamhossein biabani (توسعه اجتماعی)
The relationship between drug abuse and crime is not very clear. But the variety of relationships between these two variables depends on the particular composite of drug and kinds of crimes, as well. Many believe that drug abuse is the cause of crimes. The perception of this belief is that crime reduction can be carried out through access reduction to drug. Of course, It is not clear that there is a relationship between these two (drug and crime). This research addresses the relationship between drug and crime using descriptive-analytical method. Although a lot of studies show a relationship between drug and crime, other studies consider no relationship in this regard. Moreover, there are few studies on realizing these different findings. There is a possibility that drug and crime have interrelationship under certain conditions and there might not exist any relationship outside these conditions. Drug abuse and crime might have interrelationship in different ways. Therefore; there are various causative models pertaining the relationship between drug abuse and crime which this article will address.